PHYGITAL BANKING (PHYSICAL & DIGITAL BANKING) IN INCREASING CUSTOMER TRUST TOWARDS SUSTAINABLE LOYALTY - Wursan Wursan; Dedeh Sri Sudaryanti; Prama Permana; Agi Rosyadi; Erwin Yulianto (CV. Adiba Aisha Amira, 2025)
This research explores the link between Phygital Banking, Customer Trust, and enduring Customer Loyalty. Data was gathered from numerous bank clients in West Java, Indonesia, via an online questionnaire. The data underwent quantitative analysis using the Structural Equation Model (SEM) and was processed with SmartPLS 4.0. A total of 399 participants were assessed for validity, reliability, and hypothesis testing. Findings revealed that Customer Trust positively and significantly influences Customer Loyalty, while Phygital Banking similarly has a positive and significant impact on Customer Loyalty. Additionally, Phygital Banking strengthens the bond between Customer Trust and sustained Loyalty. This research introduces a fresh perspective on the interconnectedness of Phygital Banking, Customer Trust, and lasting Loyalty, which was absent in earlier studies. The findings emphasize the importance for banks to consistently offer both physical and digital services. Achieving this demands enhanced technology, skilled personnel, and innovative strategies. Furthermore, collaboration with governmental bodies like Bank Indonesia and the Financial Services Authority is crucial to enhance Phygital Banking offerings, foster trust among customers, and ultimately boost loyalty.